2012
DOI: 10.1002/term.1484
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing angiogenesis alleviates hypoxia and improves engraftment of enteric cells in polycaprolactone scaffolds

Abstract: We examined whether expediting angiogenesis in porous polycaprolactone (PCL) scaffolds could reduce hypoxia and consequently improve the survival of transplanted enteric cells. To accelerate angiogenesis, we delivered vascular endothelial growth factor (VEGF) using PCL scaffolds with surface cross-linked heparin. The scaffold fabrication and characterization has been reported in our previous study. Enteric cells, isolated from intestinal tissue of neonatal mice and expanded in vitro for 10 days, exhibited high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Concerns focus on any adverse environmental effects from the binding material. PCL is a biocompatible polymer [17,[30][31][32][33], providing us environmental benefit with significant reduction of undesired bacterial toxicity. We expect this study to offer a better understanding of the importance of specific endotoxin binding and material research.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns focus on any adverse environmental effects from the binding material. PCL is a biocompatible polymer [17,[30][31][32][33], providing us environmental benefit with significant reduction of undesired bacterial toxicity. We expect this study to offer a better understanding of the importance of specific endotoxin binding and material research.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, heparin was cross‐linked onto an electrospun polycaprolactone graft using carbodiimide chemistry, where the amine groups reacts with the carboxylic groups in heparin. This technique has been widely used in a number of scaffolds for other tissue engineering applications …”
Section: Discussionmentioning
confidence: 99%
“…Heparin is a naturally occurring highly sulfated glycosaminoglycan. Because of its unique structure, and consequent ability to bind, release, and protect multiple growth factors, heparin has been investigated as a drug delivery mechanism . Our group has developed a method of immobilizing heparin onto a PCL scaffold for drug delivery and showed that immobilized heparin resulted in sustained release of VEGF, which resulted in a dose‐dependent angiogenic effect when implanted subcutaneously in mice …”
mentioning
confidence: 99%
“…Hybrid constructs containing cells and fibrillar scaffolds are increasingly used as models of cellular interaction with extracellular matrix [ 1 ], or for various bioengineering applications [ 2 , 3 ]. Because of their favorable biomimetic and biomechanical properties, cell-seeded fibrillar scaffolds are considered for vascular grafting [ 4 ], as cardiovascular patches [ 5 , 6 ], or for bone reconstruction [ 7 ].…”
Section: Introductionmentioning
confidence: 99%